FORMULASI STRATEGI RANTAI PASOK TEPUNG TERIGU UNTUK INDUSTRI KECIL MENENGAH DI KABUPATEN JEMBER - Bambang Herry Purnomo; Andrew Setiawan Rusdianto; Yurika Widya Dewi (Faculty of Agricultural Technology, University of Jember, 2014)
Wheat flour is the raw material that often used by food industrial. Small and Medium Entyties has a significant contribution to Indonesian economy growth. Common problems faced by SMEs is often the price fluctuations of wheat flour and difficult to obtain wheat flour sustainability as raw material by affordable price, so it must be made supply chain management of wheat flour to handle the problems in order to increased of SMEs based wheat flour. The aim of this research is to analyze the supply chain system of wheat flour, analyze strengths and weaknesses in the supply chain, formulated supply chain strategy of wheat flour to increase the competitiveness of SMEs based wheat flour in Jember. This research was conducted in three stages, namely preliminary stage through literature, alternative determination stage using SWOT and strategy selection stage using AHP. The results is a good strategy to increase the competitiveness of SMEs based wheat flour in Jember is to increase the productivity of SMEs based wheat flour.Keywords: supply chain, wheat flour, Small and Medium Entyties (SMEs) based wheat flour, SWOT, AHP